Common prognostic factors of work disability among employees with a chronic somatic disease: a systematic review of cohort studies - Detaille, Sarah I.; Heerkens, Yvonne F.; Engels, Josephine A.; van der Gulden, Joost WJ; van Dijk, Frank JH (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVE ': 'Based on prospective and retrospective disease cohort studies, the aim of this review was to determine common prognostic factors for work disability among employees with rheumatoid arthritis, asthma, chronic obstructive pulmonary disease, diabetes mellitus, and ischemic heart disease (IHD). ' ' METHODS ': 'A systematic literature search in Medline (1990–2008) and Embase (1990–2008) was carried out to identify relevant cohort studies using a well-defined list of inclusion and quality criteria. ' ' RESULTS ': 'We identified 43 relevant cohort studies with sufficient methodological quality (20 for rheumatoid arthritis, 3 for asthma and 20 for IHD). The common prognostic factors for work disability found in all the diseases were: perceived health complaints, limitation in daily physical activities caused by the disease (high versus low), heavy manual work, and female gender. The common positive prognostic factors for rheumatoid arthritis and IHD were age (high versus low) and sickness absence. The common negative factors for rheumatoid arthritis and IHD were education (high versus low) and ethnic origin (white versus non-white). ' ' CONCLUSIONS ': 'As many prognostic factors for work disability are similar for employees with various chronic diseases, it is possible to detect high risk groups. This information supports the development and implementation of a general disability management intervention for employees suffering from a chronic disease to overcome health-related limitations at work.
Keywords: chronic disease; chronic somatic disease; cohort study; employee; occupational health; prognostic factor; review; risk factor; self-management; somatic disease; systematic review; work disability